On infinite-dimensional dissipative quadratic stochastic operators - Shahidi, Farruh (Springer, 2013)
The purpose of the paper is to extend the notion of dissipativity of maps on infinite-dimensional simplex. We study the fixed points of dissipative quadratic stochastic operators on infinite-dimensional simplex. Besides, we study the limit behavior of the trajectories of such operators. We also show the difference of dissipative operators defined on finite and infinite-dimensional spaces. We obtain the results by using majorization for infinite vectors and ℓ1 convergence.